2009
DOI: 10.1002/ajp.20718
|View full text |Cite
|
Sign up to set email alerts
|

Sterile pyuria in a population of wild white‐handed gibbons (Hylobates lar)

Abstract: Urinalysis is an emerging method for monitoring the health and energy balance of wild primates. Here, we report the first urinalysis of wild gibbons. We used multi-reagent test strips to monitor the health status of 52 individual white-handed gibbons (Hylobates lar) inhabiting Khao Yai National Park, Thailand. Most urinary reference values were within normal ranges; however, regardless of age- and sex-class or monthly fruit productivity, we found unexpectedly high rates of urinary leukocytes (50% and 90% of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The range of pH that we observed in this study (5-8) was similar to that observed among gibbons (Beaman et al 2009) and chimpanzees of West Africa (Leendertz et al 2010), but considerably less alkaline than in studies of chimpanzees in East Africa (Kaur and Huffman 2004;Krief et al 2005) and mountain gorillas (Sleeman and Mudakikwa 1998). Like ketonuria, diet is an important factor mediating urinary pH; shifting from a diet dominated by vegetables to one dominated by animal proteins will acidify urinary pH (Remer 2000(Remer , 2001Siener and Hesse 2002).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The range of pH that we observed in this study (5-8) was similar to that observed among gibbons (Beaman et al 2009) and chimpanzees of West Africa (Leendertz et al 2010), but considerably less alkaline than in studies of chimpanzees in East Africa (Kaur and Huffman 2004;Krief et al 2005) and mountain gorillas (Sleeman and Mudakikwa 1998). Like ketonuria, diet is an important factor mediating urinary pH; shifting from a diet dominated by vegetables to one dominated by animal proteins will acidify urinary pH (Remer 2000(Remer , 2001Siener and Hesse 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Reagan et al 2007). Whether high urine concentrations or pH levels are generally a cause of proteinuria remains uncertain, but given that proteins were the most commonly detected analyte in this study, and have been commonly observed in similarly small amounts in the urine of other wild primates (Beaman et al 2009;Kaur and Huffman 2004;cf. Krief et al 2005;Leendertz et al 2010), positive test results for small amounts of proteins may not indicate an underlying urological condition.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…They provide rapid screening mainly for diseases of the kidney and the urogenital tract, carbohydrate metabolism disorders (diabetes mellitus), liver diseases, and hemolytic disorders. The dip sticks are widely used in human and veterinary medicine; however, their use is not yet well documented for wild primates in general, and only a few studies contribute to baseline data on urinary parameters in wild chimpanzees [Beaman et al, 2009;Kaur & Huffman, 2004;Kelly et al, 2004;Knott, 1998;Krief et al, 2005;Sleeman & Mudakikwa, 1998]. Furthermore, the studies on chimpanzees include a relatively low number of samples collected from a limited number of months of the year, and provide data on the East African subspecies only.…”
Section: Introductionmentioning
confidence: 99%